Formulation and Evaluation of Anti-Inflammatory, Antioxidant Activity, and Safety of OBISA Herbal Oil Based on Virgin Coconut Oil as Baby Massage Oil - Sudarmi Sudarmi; St. Halimatussya’diah; Ni Putu Dian Ayu Anggraeni; Melyana Nurul Widiawati; Iswari Pauzi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The use of herbal ingredients as topical preparations continues to grow because they are considered safer and possess diverse biological activities. A combination of turmeric, coriander, kadara extracts, and clove essential oil has the potential to be developed into a herbal massage product for babies, which is highly beneficial for growth and development due to its anti-inflammatory and antioxidant activities. This study aims to formulate OBISA Herbal Oil from Virgin Coconut Oil (VCO) and to evaluate its anti-inflammatory and antioxidant activities, physical characteristics, and safety . Laboratory experimental research was conducted at the CNH Aromatherapy Laboratory, Semarang (July–September 2025). Extraction was carried out using maceration and distillation methods. Evaluations included flavonoid testing, in vitro anti-inflammatory activity (BSA protein denaturation inhibition), antioxidant activity (DPPH method), organoleptic tests, pH, homogeneity, adhesiveness, stability, and skin irritation testing. The turmeric extract showed the highest flavonoid content (6617.93 mg QE/100 g). Antioxidant activity increased with concentration, with the highest inhibition observed in the 1.5% formula (85.5%). The best anti-inflammatory activity was found in the 0.5% formula. The 1% formula demonstrated optimal adhesion and stable physical characteristics. Irritation tests showed an irritation index of 0 (non-irritant). OBISA Herbal Oil is safe for topical use with good biological activity. The 1% formula is the most optimal formulation based on effectiveness and physical quality